The profile and prognostic significance of bone marrow T-cell differentiation subsets in adult AML at diagnosis - Sun, Kai; Shi, Zong-Yan; Wang, Ya-Zhe; Xie, Dai-Hong; Liu, Yan-Rong; Jiang, Qian; Jiang, Hao; Huang, Xiao-Jun; Qin, Ya-Zhen (Frontiers in Immunology, 2024)
Background T lymphocytes in tumor microenvironment play a pivotal role in the anti-tumor immunity, and the memory of T cells contributes to the long-term protection against tumor antigens. Compared to solid tumors, studies focusing on the T-cell differentiation in the acute myeloid leukemia (AML) bone marrow (BM) microenvironment remain limited. Patients and methods Fresh BM specimens collected from 103 adult AML patients at diagnosis and 12 healthy donors (HDs) were tested T-cell differentiation subsets by multi-parameter flow cytometry. Results CD4 and CD8 T-cell compartments had different constituted profiles of T-cell differentiated subsets, which was similar between AML patients and HDs. Compared to HDs, AML patients as a whole had a significantly higher proportion of CD8 effector T cells (Teff, P = 0.048). Moreover, the T-cell compartment of AML patients with no DNMT3A mutations skewed towards terminal differentiation at the expense of memory T cells (CD4 Teff: P = 0.034; CD8 Teff: P = 0.030; CD8 memory T: P = 0.017), whereas those with mutated DNMT3A had a decrease in CD8 naïve T (Tn) and CD4 effector memory T cells (Tem) as well as an increase in CD4 central memory T cells (Tcm) (P = 0.037, 0.053 and 0.053). Adverse ELN genetic risk correlated with a lower proportion of CD8 Tn. In addition, the low proportions of CD4 Tem and CD8 Tn independently predicted poorer relapse-free survival (RFS, HR [95%CI]: 5.7 (1.4-22.2), P = 0.017 and 4.8 [1.3-17.4], P = 0.013) and event-free survival (EFS, HR [95% CI]: 3.3 (1.1-9.5), P = 0.029; 4.0 (1.4-11.5), P = 0.010), respectively. Conclusions AML patients had abnormal profiles of BM T-cell differentiation subsets at diagnosis, which was related to DNMT3A mutations. The low proportions of CD4 Tem and CD8 Tn predicted poor outcomes.